Axisymmetric Stagnation-Point Flow of Nanofluid over a Stretching Surface (Advances in Applied Mathematics and Mechanics, 2014)
This paper investigates the laminar boundarylayer flow of nanofluid induced by a radially stretching sheet. Nanofluidmodel exhibiting Brownian motion and thermophoresis is used. Seriessolutions for a reduced system of nonlinear ordinary differential equationsare obtained by homotopy analysis method (HAM). Comparative study betweenthe HAM solutions and previously published numerical results shows anexcellent agreement. Velocity, temperature and mass fraction are displayedfor various values of parameters. The local skin friction coefficient, thelocal Nusselt number and the local Sherwood number are computed. It isobserved that the presence of nanoparticles enhances the thermalconductivity of base fluid. It is found that the convective heat transfercoefficient (Nusselt number) is decreased with an increase in concentrationof nanoparticles whereas Sherwood number increases when concentration ofnanoparticles in the base fluid is increased.